The Effect of E-Service Quality and E-Trust Whatsapps Reminder on Loyalty Through Customer Satisfaction BPJS Ketenagakerjaan Banyuwangi Regency - Muhammad Rodhita Arfiandi; Muhammad Firdaus; Tamriatin Hidayah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of e-service quality and e-trust Whatsapp Reminder on customer loyalty of BPJS Ketenagakerjaan Banyuwangi Regency with customer satisfaction as an intervening variable. In the digital era, technology-based services are a key factor in improving customer experience, especially in social security services. This study uses a quantitative approach with a survey method involving 100 respondents of BPJS Ketenagakerjaan Banyuwangi Regency participants who have used the Whatsapp Reminder service. Data was collected through questionnaire methods and direct interview sampling and then analyzed using the Smart PLS method. This Smart PLS analysis method used to analyze data is the value of Path Coefficients, P-value, and T-Statistics. The results showed that e-service quality and e-trust Whatsapp Reminder have a positive and significant influence on customer satisfaction. In addition, customer satisfaction acts as a mediator that strengthens the relationship between e-service quality and e-trust Whatsapp Reminder on customer loyalty. Thus, improving the quality of digital services and trust in the WhatsApp Reminder system contribute directly to BPJS Ketenagakerjaan customer loyalty. These findings provide implications for service managers for BPJS Ketenagakerjaan participants to continue to improve digital service quality and build customer trust in order to maintain loyalty in the long term.